Tetralogy of Fallot and hypertrophic cardiomyopathy in a case of cardiofaciocutaneous syndrome - Yıldırım, Selman Vefa; Kale-Çekinmez, Eren; Özcan, Deren; Derbent, Murat (The Turkish Journal of Pediatrics, 2008)
Cardiofaciocutaneous (CFC) syndrome is a rare disorder characterized by psychomotor and growth retardation, a typical facial dysmorphism, congenital heart defects, and ectodermal abnormalities. Pulmonic stenosis, atrial and ventricular septal defects, patent ductus arteriosus, and hypertrophic cardiomyopathy are cardiac findings identified in patients with this syndrome; however, tetralogy of Fallot has never been associated with CFC syndrome. CFC should be considered in patients with skin abnormalities in addition to phenotypic features and a congenital heart defect, including tetralogy of Fallot.